2008
DOI: 10.1128/jvi.01278-08
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Replication of Porcine Endogenous Retrovirus and Porcine Lymphotropic Herpesvirus Type 1 with Prolonged Pig Cell Microchimerism after Pig-to-Baboon Xenotransplantation

Abstract: Porcine endogenous retrovirus (PERV), porcine cytomegalovirus (PCMV), and porcine lymphotropic herpesvirus (PLHV) are common porcine viruses that may be activated with immunosuppression for xenotransplantation. Studies of viral replication or transmission are possible due to prolonged survival of xenografts in baboon recipients from human decay-accelerating factor transgenic or ␣-1,3-galactosyltransferase gene knockout miniature swine. Ten baboons underwent xenotransplantation with transgenic pig organs. Graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 50 publications
3
39
0
Order By: Relevance
“…Consistent with this notion PLHV-1 DNA was detected in peripheral blood mononuclear cells (PBMCs) and plasma of recipient baboons after pig organ solid organ transplantation [10 ]. Productive infection was absent, and in all cases pig cell microchimerism was found.…”
Section: Porcine Lymphotropic Herpesvirussupporting
confidence: 50%
See 1 more Smart Citation
“…Consistent with this notion PLHV-1 DNA was detected in peripheral blood mononuclear cells (PBMCs) and plasma of recipient baboons after pig organ solid organ transplantation [10 ]. Productive infection was absent, and in all cases pig cell microchimerism was found.…”
Section: Porcine Lymphotropic Herpesvirussupporting
confidence: 50%
“…Pig donors originating from a special designated pathogen-free herd were free of PCMV DNA [9]. In a separate trial of pig solid organ transplantation into baboon recipients PCMV DNA was detected in baboon blood samples after transplantation only in two recipients who had received organs from swine donors raised prior to the institution of an early weaning strategy to exclude PCMV [10 ].…”
Section: Porcine Cytomegalovirusmentioning
confidence: 99%
“…Studies have demonstrated that early weaning of piglets is an effective method for maintaining the donor organs free of CMV, thus negating risks of PCMV reactivation in the recipient primate following organ transplantation [4,8]. However, the finding in the present study of one PCMV‐positive donor tissue raises the question of whether early‐weaning is entirely effective, and indicates that periodic assessment of the PCMV status of the donor pig herd is warranted.…”
Section: Organs and Tissues Tested For Cytomegalovirus (Cmv) In The mentioning
confidence: 68%
“…The clinical symptoms of experimental porcine PTLD, such as fever, lethargy, anorexia, high white blood cell count, and palpable lymph nodes, are similar to those of human PTLD, which was linked to the human herpesvirus Epstein-Barr virus, now designated HHV-4 [77]. Evidence of productive PLHV-1 infection was not detected in recipient baboons receiving different organs from transgenic pigs for up to 6 months of transplant function [78]. Appropriate breeding procedures can eliminate PLHV and piglets free of PLHV were produced via Caesarean section and barrier-reared breeding procedure [74].…”
Section: Microbiological Safetymentioning
confidence: 81%